Recombinant VP7-Based Enzyme-Linked Immunosorbent Assay for Detection of Immunoglobulin G Antibodies to Colorado Tick Fever Virus - Mohd Jaafar, Fauziah (American Society for Microbiology, 2003)
VP6, VP7, VP9, VP10, VP11, and VP12 of Colorado tick fever virus (CTF virus), a virus member of the genus Coltivirus, family Reoviridae, were expressed in bacteria with the pGEX-4T-2 vector. A partial sequence of VP7 (designated pVP7) was chosen to elaborate an enzyme-linked immunosorbent assay (ELISA) for detecting anti-CTF virus immunoglobulin G (IgG) antibodies in humans. This was based on two observations: (i) among all expressed proteins, pVP7 showed the highest immunoreactivity to an anti-CTF virus hyperimmune ascitic fluid; (ii) to provide the highest selectivity of antibody detection, the expressed sequence was chosen within a region which is highly divergent (49% amino acid identity) from the homologous sequence of another coltivirus, the Eyach virus. The pVP7 ELISA was evaluated with 368 serum samples from French blood donors and found to provide 98.1% specificity. Assays with the Calisher set of human serum samples, positive for anti-CTF virus antibodies (C. H. Calisher, J. D. Poland, S. B. Calisher, and L. A Warmoth, J. Clin. Microbiol. 22:84-88, 1985), showed that the pVP7 ELISA provided 100% sensitivity for the tested population. After elaboration of recombinant-protein-based ELISAs for diagnosis of infections with members of the viral genera Orbivirus, Orthoreovirus, and Rotavirus, it was shown that a recombinant protein could be used to detect antibodies to the human pathogen Colorado tick fever virus.